Analisis diskriminasi sosial terhadap orang dengan gangguan mental dalam komunitas Muslim di Indonesia: Perspektif keagamaan dan kultural - Sopiandi Harahap, Mulia; Mulhim Hidayat, Indra; Rangkuty, Panigoran; Zaman, Nurul (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
This study aims to analyze the forms and factors of social discrimination against people with mental disorders (PMD) within Muslim communities in Indonesia from religious and cultural perspectives. Using a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, and document analysis. The findings reveal that social discrimination against PMD arises from the complex interaction between narrow religious interpretations and deeply rooted cultural norms of shame. Religious views emphasizing the sanctity of worship spaces, combined with social expectations of “normality,” often lead to the exclusion of PMD from religious and community activities. Nevertheless, some Muslim communities have begun integrating the Islamic principle of rahmatan lil ‘alamin with mental health literacy in education and da’wah, which significantly reduces stigma and promotes social acceptance. This study highlights the necessity of integrating religious, psychological, and cultural values to develop an inclusive and equitable Islamic education praxis that upholds human dignity and mental well-being.